Tratamiento de ruptura del tendón calcáneo común en un canino con sistema crimp-clamp: Reporte de caso - Troncoso, Ignasio (2025)
Rupture of the common calcaneal tendon is a common injury in dogs, primarily due to traumatic causes. Several surgical techniques have been described as treatments for these injuries, the main objective being to restore adequate tensile strength to support body weight. Because the tendon is poorly vascularized and constantly subjected to tension, the healing process is often complex and time-consuming. Providing postoperative stability is vital for achieving proper healing. Various joint fixation methods have been used, but these are often associated with complications due to prolonged use. This report describes a German Shepherd patient with a rupture of the common calcaneal tendon. The patient was surgically treated using a Bunnel-Mayer suture pattern combined with the crimp clamp system and a Steinmann calcaneotibial nail as a temporary joint immobilizer. The surgical technique, short- and long-term results, and the complications presented are discussed.